Do airport activities affect regional economies? Regional analysis of New Zealand's airport system. Issue 4 (3rd April 2021) - Fu, Xiaowen; Hong Tsui, Kan Wai; Sampaio, Breno; Tan, David
ABSTRACT: This study investigates the impacts of airport activities on regional economies using annual data on all regions and 22 airports in New Zealand from 2001 to 2016. In addition to fixed effects estimation, the system generalized method of moments approach and the dynamic common correlated effects estimator are used to account for cross-sectional dependence, cross-regional heterogeneity and feedback effects. The study shows clear and consistent evidence that aviation activities positively affect regional economies, and that it is beneficial for policy-makers and airport owners in a region to promote aviation activities.